Wielki mały człowiek w bikornie. O ikonografii potęgi i upadku Napoleona na kartach pocztowych z pierwszych dekad XX wieku - Pawłowska-Jądrzyk, Brygida (Załącznik Kulturoznawczy, 2022)
The huge popularity of mass-produced images of Napoleon Bonaparte (lithographs, statuettes, busts, plates etc.) lasted throughout the 19th century until 1914 in many countries. It can be assumed that the vitality of these trends in the popular circulation of culture at the beginning of the 20th century until the outbreak of World War I is evidenced by illustrations reproduced on postcards, which are then gaining more and more recognition as a new form of interpersonal communication and as a collector’s item. The author of the article analyzes the postcard representations of Napoleon, paying special attention to the symbolic aspects of the headgear in which the great Corsican was presented. Napoleon fascinated as a great leader, but also as a “fallen colossus”. The article shows, inter alia, that ever since the romanticism human imagination succumbed to the mocking vision of Bonaparte’s lonely end on a distant island. Such representations, very widespread thanks to postcards at the beginning of the 20th century, inevitably transform the defeat, suffering and death of a fallen hero into a “sentimental idyll”, making Napoleon one of the most powerful rulers of the collective imagination and, in a sense, the king of kitsch.